Effect of active Aβ immunotherapy on neurons in human Alzheimer's disease. Issue 5 (7th January 2015) - Paquet, Claire; Amin, Jay; Mouton‐Liger, François; Nasser, Mariam; Love, Seth; Gray, Françoise; Pickering, Ruth M; Nicoll, James AR; Holmes, Clive; Hugon, Jacques; Boche, Delphine
Abstract: Amyloid β peptide (A β ) immunization of Alzheimer's disease (AD) patients has been reported to induce amyloid plaque removal, but with little impact on cognitive decline. We have explored the consequences of A β immunotherapy on neurons in post mortem brain tissue. Eleven immunized (AN1792, Elan Pharmaceuticals) AD patients were compared to 28 non‐immunized AD cases. Immunohistochemistry on sections of neocortex was performed for neuron‐specific nuclear antigen (NeuN), neurofilament protein (NFP) and phosphorylated‐(p)PKR (pro‐apoptotic kinase detected in degenerating neurons). Quantification was performed for pPKR and status spongiosis (neuropil degeneration), NeuN‐positive neurons/field, curvature of the neuronal processes and interneuronal distance. Data were corrected for age, gender, duration of dementia and APOE genotype and also assessed in relation to A β 42 and tau pathology and key features of AD. In non‐immunized patients, the degree of neuritic curvature correlated with spongiosis and pPKR, and overall the neurodegenerative markers correlated better with tau pathology than A β 42 load. Following immunization, spongiosis increased, interneuronal distance increased, while the number of NeuN‐positive neurons decreased, consistent with enhanced neuronal loss. However, neuritic curvature was reduced and pPKR was associated with A β removal in immunized patients. In AD, associations of spongiosis status, curvature ratio and pPKR load with microglial markers Iba1, CD68 and CD32 suggest a role for microglia in neurodegeneration. After immunization, correlations were detected between the number of NeuN‐positive neurons and pPKR with Iba1, CD68 and CD64, suggesting that microglia are involved in the neuronal loss. Our findings suggest that in established AD this form of active A β immunization may predominantly accelerate loss of damaged degenerating neurons. This interpretation is consistent with in vivo imaging indicating an increased rate of cerebral atrophy in immunized AD patients. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.